IL-34 Upregulated Th17 Production through Increased IL-6 Expression by Rheumatoid Fibroblast-Like Synoviocytes. (4th June 2017) - Wang, Bing; Ma, Zijian; Wang, Miaomiao; Sun, Xiaotong; Tang, Yawei; Li, Ming; Zhang, Yan; Li, Fang; Li, Xia
Abstract : Rheumatoid arthritis (RA) is a chronic autoimmune disease which is characterized by synovial inflammation and cartilage damage for which causes articular dysfunction. Activation of fibroblast-like synoviocytes (FLS) is a critical step that promotes disease progression. In this study, we aimed to explore the effect of interleukin-34 (IL-34) on RA FLS as a proinflammatory factor and IL-34-stimulated FLS on the production of Th17. We found that serum IL-34 levels were increased compared to those of the healthy controls and had positive correlations with C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), rheumatoid factor (RF), and anticyclic citrullinated peptide (CCP) antibody accordingly. CSF-1R was also highly expressed on RA FLS. The interaction of IL-34 and CSF-1R promoted a dramatic production of IL-6 by FLS through JNK/P38/NF- κ B signaling pathway. Further, the IL-34-stimulated IL-6 secretion by RA FLS was found to upregulate the number of Th17. The treatment of IL-6R antagonist could attenuate the production of Th17 mediated by IL-34-stimulated RA FLS. Our results suggest that the increased IL-34 levels were closely related to the disease activity of RA. Additionally, the overexpression of IL-6 in the IL-34-stimulated FLS promoted the generation of Th17. Therefore, IL-34 was supposed to be involved in the pathogenesis of RA. The inhibition of IL-34 might provide a novel target for therapies of RA.